Answer:
(3, 2)
Step-by-step explanation:
Given the 2 equations
y = 2x - 4 → (1)
3x + y = 11 → (2)
Substitute y = 2x - 4 into (2)
3x + 2x - 4 = 11
5x - 4 = 11 ( add 4 to both sides )
5x = 15 ( divide both sides by 5 )
x = 3
Substitute x = 3 into (1) for corresponding value of y
y = (2 × 3) - 4 = 6 - 4 = 2
Solution is (3, 2)
Answer:
1. the answer is nonfictional story about a person, topic, or event
Step-by-step explanation:
hope this helps
Let's make an equation. T will be the number.
(T+5)/4=7
Let's multiply both sides by 4 to get T by itself.
T+5=28
Subtract 5 from both sides.
T=23
Your number is 23.
Answer:-y,x
Step-by-step explanation: It is rotateing into the negative part of a graph if you think about it.
For this fraction, you would have to see how many times 7 goes into 47. So, 6 times as 7 times 6 is 42. Subtract 42 from 47, and this would be your remainder:
6